Protein Consumption: Inadequacy in Amount, Food Sources, and Mealtime Distribution in Community-Dwelling Older Adults. - Gaspareto, Natália; Previdelli, Ágatha Nogueira; Laurentino, Gilberto Candido; de Aquino, Rita de Cássia (Ageing International, 2023)
Adequate protein consumption in amount, food sources, and meals is important to maintain muscle mass and reduce the risk of sarcopenia in older adults. This study aimed to assess protein intake in terms of the amount consumed, food sources, and meals in a sample of 295 community-dwelling older adults in a city in southeastern Brazil. Protein intake was assessed in grams/day and the amount consumed per meal and food sources were calculated using the total value and relative contribution. Adequate protein consumption was considered 0.66 g/kg/day (Estimated Average Requirement-EAR) and amount per meal 25 g, as recommended by the PROT-AGE Study Group. Descriptive analysis was based on central trend and dispersion measures. Average protein intake was 67 g and 1.05 g/kg, with an 8.5% prevalence of inadequacy. The meal that provided the largest protein contribution was lunch and 98% of the group showed insufficient intake at breakfast. Concerning food sources, the greatest contribution came from the meat group (47.3%). The results indicated that median intake was at the lower end of the range recommended by PROT-AGE, with about 50% of subjects consuming less than 1.0 g/kg/day. Protein distribution among meals showed a high prevalence of adequate consumption, breakfast being the most critical meal. Strategies to optimize protein intake should consider the amount, quality, and distribution of protein consumed at meals that form part of a balanced healthy diet, in addition to dietary techniques and supplementation, to achieve maximum protein synthesis capacity.